CO-BRANDING PADA DESAIN KEMASAN SILVERQUEEN X WONDERFUL INDONESIA DALAM PERSPEKTIF SOSIOLOGI DESAIN : CO-BRANDING IN THE PACKAGING DESIGN OF SILVERQUEEN X WONDERFUL INDONESIA FROM THE PERSPECTIVE OF THE SOCIOLOGY OF DESIGN - Monica Revias Purwa Kusuma; Brilindra Pandanwangi; Rian Prasetya Yunanto; Zahra Titania Magenta (Jurnal Dimensi Seni Rupa dan Desain, 2026)
Amidst globalization, local cultural identity has become strategic. Wonderful Indonesia (WI) engaged in a co-branding collaboration with SilverQueen, launching 5 special edition #IniIndonesiaku packages (July 2023). This research examines how the packaging, as a cultural text, is encoded (represented) by the producer and decoded (perceived) by Gen Z consumers, using Stuart Hall's theory. This qualitative case study method used interviews (10 Gen Z respondents) and visual observation. The encoding results show the producer constructed an ideal, harmonious, and diverse image of Indonesia by uniting high and pop culture, stereotypical diversity, and maritime identity. The Gen Z decoding results split into three positions: Dominant (fully accepting the "very Indonesian" meaning), Negotiated (accepting the general message but criticizing specific elements like "boring" colors), and Oppositional (rejecting it due to "too basic" symbols, lack of narrative, and an "outdated" art style). In conclusion, a significant gap exists not in the cultural symbols (denotation), but in the visual execution (connotation) which did not align with Gen Z aesthetics.